2016
DOI: 10.1155/2016/5718580
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effects of Smartphone Push Notifications on Task Performance with regard to Smartphone Overuse Using ERP

Abstract: Smartphones are used ubiquitously worldwide and are essential tools in modern society. However, smartphone overuse is an emerging social issue, and limited studies have objectively assessed this matter. The majority of previous studies have included surveys or behavioral observation studies. Since a previous study demonstrated an association between increased push notifications and smartphone overuse, we investigated the effects of push notifications on task performance. We detected changes in brainwaves gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
22
3
2
Order By: Relevance
“…Smartphones, and especially certain cues associated with new incoming information or messages, have an explicit demanding character and are able to induce craving to use online-communication applications 71 . Auditory smartphone notifications were shown to attract attention and affect task performance, especially in individuals with a tendency towards an excessive use 72 . Cognitive control processes are necessary in order to inhibit or ignore impulsive responses on demanding cues in situations, when responding to the auditory signals is not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones, and especially certain cues associated with new incoming information or messages, have an explicit demanding character and are able to induce craving to use online-communication applications 71 . Auditory smartphone notifications were shown to attract attention and affect task performance, especially in individuals with a tendency towards an excessive use 72 . Cognitive control processes are necessary in order to inhibit or ignore impulsive responses on demanding cues in situations, when responding to the auditory signals is not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Park and colleagues [2] proposed that smartphone popularity is due to the ease and flexibility with which they can be used to complete daily tasks. While there are many advantages of smartphone use, there are also negative effects, such as: nomophobia [3], smartphone involvement [4], dependency [5] and distraction [6]. Furthermore, notification settings and proximity to one's smartphone can evoke feelings of inattention, hyperactivity [7] and anxiety [8].…”
Section: Introductionmentioning
confidence: 99%
“…Seo and colleagues [9] discovered that mobile phone use negatively predicted attention which in turn affected mathematics and language arts achievement. Newer studies have found that receiving notifications or a call during a task can affect task performance [6,10]. Kim and colleagues [6] examined the effects of notifications on task performance with regards to smartphone overuse and found that participants in the high overuse (risk) group were more sensitive to notifications than the low overuse group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations